2014
DOI: 10.3233/jad-131934
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Inhibition of Return in Mild Cognitive Impairment: Is it Specific to the Presence of Prodromal Dementia?

Abstract: Although there is some evidence that amnestic mild cognitive impairment (aMCI) can be characterized by significant deficits in visuospatial function, the cross-sectional design of the majority of these studies renders it impossible to determine whether such deficits occur in aMCI as a result of, or accompany, amnestic dysfunction per se or whether they are the result of disproportionately poorer performance in a sub-group of patients for whom aMCI represents prodromal dementia. Similarly, whether the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Although we identified 22 studies that met our inclusion criteria, several of these involved samples drawn from the same study population. Specifically, the PATH Through Life Study Das et al, 2014), Project MIND (Bielak, Hultsch, Strauss, MacDonald, & Hunter, 2010a, 2010bGrand, Stawski, & MacDonald, 2016;Yao, Stawski, Hultsch, & MacDonald, 2016), the Victoria Longitudinal Study (Bielak, Hughes, Small, & Dixon, 2007;MacDonald, Hultsch, & Dixon, 2003, 2008Whitehead, Dixon, Hultsch, & MacDonald, 2011), the West of Scotland Twenty-07 Study (Deary & Der, 2005a, 2005b, while two further studies used identical participants (Bayer et al, 2014;Tales et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we identified 22 studies that met our inclusion criteria, several of these involved samples drawn from the same study population. Specifically, the PATH Through Life Study Das et al, 2014), Project MIND (Bielak, Hultsch, Strauss, MacDonald, & Hunter, 2010a, 2010bGrand, Stawski, & MacDonald, 2016;Yao, Stawski, Hultsch, & MacDonald, 2016), the Victoria Longitudinal Study (Bielak, Hughes, Small, & Dixon, 2007;MacDonald, Hultsch, & Dixon, 2003, 2008Whitehead, Dixon, Hultsch, & MacDonald, 2011), the West of Scotland Twenty-07 Study (Deary & Der, 2005a, 2005b, while two further studies used identical participants (Bayer et al, 2014;Tales et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…One such study assessed 1. (Bayer et al, 2014;Tales et al, 2012). However, as converters were also more cognitively impaired at baseline, it is unclear whether these results would remain if absolute baseline differences in cognition were controlled for.…”
Section: Associations Between Variability and Outcomementioning
confidence: 99%
“…Early studies suggest that spatial IOR is relatively preserved in AD [8][9][10] . By contrast, more recent studies suggest that spatial IOR may be impaired in individuals with MCI or AD [11][12][13] , and IOR deficits in individuals with MCI may be predictive of conversion to dementia 13 . Most previous studies employed the classic single cuetarget paradigm 2 .…”
Section: Introductionmentioning
confidence: 89%
“…As some of these functions or component processes have been found to be abnormal in AD and/or MCI [94][95][96][97], generally in studies in Research Andrea Tales which participants with anxiety disorders have been excluded, the detrimental effect may be exacerbated further in individuals with various forms of anxiety. It is possible that everyday environmental interpretation and response, highly dependent upon vision and attentionrelated function, may be significant poorer in MCI and dementia compared to cognitively healthy ageing, as a result, at least in part, of concomitant anxiety in these disorders.…”
Section: Anxiety and Attention-related Processingmentioning
confidence: 99%
“…In addition to the traditional aspects of cognitive function explored in older adulthood, SCI, MCI and dementia, particularly in relation to diagnosis and progression, research has revealed that many other components and levels of information processing, particularly those related to attention [94][95][96][97], can also be abnormal in these conditions. However, the potential impact of anxiety upon such function remains a relative unknown and in the following section we highlight evidence related to the possibility that anxiety may directly or indirectly influence the results of both clinical and research tests of attention-related function.…”
Section: Anxiety and Clinical And Research Test Performancementioning
confidence: 99%